Ideal Point Method Applied in Forest Harvest Regulation - 秦安臣 赵林森 刘建国 李维忠 才丁华 (Journal of forestry research, 1997)
Ideal point method is one of the methods to solve multi-objective problem. It is applied to forest harvest regulation, and showed very good results by analyzing changes of quantitative indexes of forest resource structure before and after the regulation. This method can be applied as one of the mathematical tools in forest harvest regulation.